2005
DOI: 10.3171/jns.2005.102.3.0513
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of heparanase in glioblastoma multiforme

Abstract: These results indicate that the expression of heparanase was downregulated in GBM in vivo, which rarely metastasizes to distant organs outside the central nervous system. Heparanase is not implicated in the invasiveness of GBM to surrounding healthy brain tissue in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…The present data are also consistent with previous reports that describe a positive correlation between heparanase expression and tumor progression in cases of bladder, colon, pancreatic, hepatocellular, oral, gastric, esophageal, cervical, non–small cell lung, and head and neck cancers (13–22) . In contrast, it has also been reported that the expression of heparanase is downregulated in glioblastoma multiforme and in prostate cancer (23,24) . These findings suggest, however, that heparanase expression may contribute to the progression of the majority of malignant solid tumors.…”
Section: Discussionsupporting
confidence: 93%
“…The present data are also consistent with previous reports that describe a positive correlation between heparanase expression and tumor progression in cases of bladder, colon, pancreatic, hepatocellular, oral, gastric, esophageal, cervical, non–small cell lung, and head and neck cancers (13–22) . In contrast, it has also been reported that the expression of heparanase is downregulated in glioblastoma multiforme and in prostate cancer (23,24) . These findings suggest, however, that heparanase expression may contribute to the progression of the majority of malignant solid tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Moderately elevated expression of HPSE in the glioma cell line U87 resulted in increased invasion in vitro and tumor size after xenografting, but further increases in HPSE levels resulted in reduced in vitro proliferation and in vivo tumor growth [119]. In another report, HPSE was not found in human GBM, and after injection of U87 into the immunocompromised mouse brain, HPSE expression was lost [120]. When comparing HPSE expression across oligodendroglioma, anaplastic astrocytoma, and GBM, the authors did not find a correlation between HPSE and WHO grade, although the expression level was higher than in normal brain [121].…”
Section: Glioma-associated Changes In the Ecm Include Alterations In mentioning
confidence: 99%
“…In multiple myeloma, a number of oncogenic functions for HPSE have been identified including direct effects on tumor cells and indirect effects on tumor-associated endothelial cells (10,23,2325). In the brain, HPSE has been implicated in metastatic tumor cell invasion and medulloblastoma cell signaling (2628), but its role in GBM is less established (29,30) although recent studies suggest its importance in tumor progression (31). …”
Section: Introductionmentioning
confidence: 99%